A deep learning approach for object detection of rockfish in challenging underwater environments - Liu, Mingxin; Jiang, Wencheng; Hou, Mingxin; Qi, Zihua; Li, Ruixin; Zhang, Chun (Frontiers in Marine Science, 2023)
Preserving the marine ecological environment and safeguarding marine species is a global priority.However, human overfishing has led to a drastic decline in fish species with longer growth cycles, disrupting the equilibrium of the marine ecosystem. To address this issue, researchers are turning to deep learning techniques and state-of-the-art underwater devices, such as underwater robots, to explore the aquatic environment and monitor the activities of endangered populations. This approach has emerged as a focal point of recent research in protecting the marine ecological environment. This study employs a deep learning-based object detection algorithm to identify fish species in complex underwater environments. The algorithm is built upon the You Only Look Once version 7(YOLOv7) algorithm, with the addition of the attention mechanism Convolutional Block Attention Module (CBAM) in the network's backbone. CBAM enhances the feature maps through the fusion of spatial attention and channel attention, ultimately improving the robustness and accuracy of the model's inference by replacing the original loss function CIoU with SCYLLA-Intersection over Union(SIoU). In this paper, the rockfish pictures in the dataset Label Fishes in the Wild published by the National Marine Fisheries Service are selected, and the underwater image enhancement model (UWCNN) is introduced to process the pictures, and the experimental results show that the mean average precision (mAP) value of the improved model on the test set is 94.4%, which is 3.5% higher than the original YOLOv7 model, and the precision and recall rate are 99.1% and 99%, respectively. The detection performance of the algorithm in the field of complex underwater environment is improved. The underwater fish detection scheme proposed in this study holds significant practical value and significance in promoting the conservation of marine ecosystems and the protection of fish species.